Synergistic effects of BAP and kinetin media additives on regeneration of vetiver grass (Vetiveria zizanioides L. Nash) - Kanokporn Sompornpailin; Chonnikarn Khunchuay (My University, 2016)
Regeneration efficiency was enhanced by adding auxin and cytokinin at different concentrations to the media.It was found that the two highest frequencies-90 and 85%-of callus induction occured when the buds were cultured in an MS medium supplemented with 2 mgL -1 α-naphthalene acetic acid (NAA) plus 1 mgL -1 N 6 -benzylaminopurine (BAP) (CIM2) and in the same medium supplemented with 2 mgL -1 NAA plus 1 mgL -1 kinetin (CIM5), respectively.When cultured further in a plant regeneration medium supplemented with 1 mgL -1 NAA and 2 mgL -1 BAP (PRM1), these calli regenerated with high efficiencies, 80% for calli grown in CIM2 and 85% for calli grown in CIM5.The low BAP concentration in CIM1 (2 mgL -1 NAA and 0.5 mgL -1 BAP) resulted in a low regeneration efficiency and fewer shoots per callus even though the PRM3 regeneration medium had a high concentration of cytokinins (2 mgL -1 BAP and 2 mgL -1 kinetin) .However, the calli cultured in CIM2 without kinetin but with a suitable level of BAP still regenerated with high efficiencies in PRM2 and PRM3 that contained 1 and 2 mgL -1 kinetin, respectively.Similarly, when calli cultured in CIM5 without BAP but with kinetin were regenerated in PRM1 with BAP alone, they also regenerated with a high regeneration efficiency.These results showed that culturing a specific tissue in a medium with suitable concentrations of NAA and BAP or kinetin resulted in a large number of multiple shoots, and BAP and kinetin worked synergistically to produce a high plant regeneration efficiency.
Keywords: Kinetin; Callus; Turfgrass Adaptation and Management